DNA Isolation And Amplification of the rbcL (ribulose-1,5- bisphosphate carboxylase/oxygenase large subunit) gene of Caulerpa sp., Gracilaria sp., And Sargassum sp. - Biondi Tampanguma; Grevo S. Gerung; Veibe Warouw; Billy Th Wagey; Stenly Wulllur; Deiske A. Sumilat; Hens Onibala (Sam Ratulangi University, 2020)
DNA isolation and gene amplification of algae are significantly influenced by various factors such as characteristics and components of the algae cell wall. Therefore techniques and methods of DNA isolation in certain algae, sometimes only succeed in one particular species and can not be applied to another algae species. Based on that issue, this study was conducted with the aims to determine the succeed of DNA isolation and amplify the rbcL gene as a target gene for identification. Algae DNA was isolated by using innuPrep Plant DNA commercial kit, and the second one with a modified conventional Cetyl Trimetyl Ammonium Bromide (CTAB) method,Â for the amplification process was using rbcL gene (ribulose-1,5-bisphosphate carboxylase / oxygenase large subunit) with two pairs of primers : rbcL 7F-753R and rbcL 577F-rbcSR. The results showed that the DNA of Gracilaria sp was succeed isolated by using CTAB method and it was denoted by the presence of DNA bands in agarose gel. Meanwhile DNA amplification for Gracilaria sp., and Sargassum sp., were succeed amplified with the appearance of DNA bands. But in algae Caulerpa sp., was only succeed on 1 pair of primary rbcL 7F and 7.Keywords : DNA, gene rbcL, algae Caulerpa sp., Sargassum sp., Gracilaria sp;AbstrakIsolasi DNA dan amplifikasi gen pada alga sangat dipengaruhi oleh beberapa faktor seperti karakter dan komponen pada dinding sel alga. Oleh karena itu proses isolasi DNA terkadang bisa berhasil pada satu jenis alga, namun tidak berhasil pada jenis alga lainnya. Oleh karena alasan tersebut, maka penelitian ini dilakukan untuk menentukan keberhasilan Isolasi DNA dan mengamplifikasi gen rbcL sebagai gen target identifikasi. Penelitian ini dilakukan dengan tahapan awal Isolasi DNA yang menggunakan kit komersil innuPrep Plant DNA Kit, dan metode konvensional Cetyl Trimetyl Ammonium Bromide (CTAB) yang telah dimodifikasi. Sedangkan untuk proses amplifikasi, menggunakan gen rbcL (ribulose-1,5-bisphosphate carboxylase/oxygenase large subunit) digunakan dua pasang primer yaitu rbcL 7F-753R dan rbcL 577F-rbcSR. Hasil isolasi DNA dari alga Gracilaria sp berhasil diisolasi menggunakan metode CTAB yang ditandai dengan adanya pita DNA pada gel agarose. Amplifikasi DNA pada alga Gracilaria sp., dan Sargassum sp., berhasil diamplifikasi dengan munculnya pita DNA. Namun pada alga Caulerpa sp. hanya berhasil pada 1 pasang primer rbcL 7F dan753R.Kata kunci : DNA, gen rbcL, alga Caulerpa sp., Sargassum sp., Gracilaria sp.